Communication Patterns of Islamic Religious Education Teachers and Parents in the Covid-19 Pandemic - Ali Akbarjono; Nina Siti Salmaniah Siregar; Erniwati La Abute; Ahmad Zainuri (STAI Hubbulwathan Duri, 2021)
Islamic Religious Education teachers need to establish harmonious relationships with parents and students during the Covid-19 Pandemic even though students study from home, so communication between teachers and parents is required to supervise their children’s learning at home. This study aims to analyze the communication patterns used by Islamic Religious Education teachers and parents during the Covid-19 Pandemic and the supporting and inhibiting factors in Junior High Schools. The research method used is descriptive qualitative with a phenomenological approach. Data were collected through in-depth interviews with structured interview techniques. Tool for organizing data with Thematic Analysis. Then the data were analyzed by the Colaizzi method. This study concludes that the communication pattern used by Islamic Religious Education teachers and parents is a secondary or two-way communication pattern. Harmonious communication between teachers and parents supports student and teacher learning success. Thus, the communication needs to be carried out intensely and continuously and involves other school members such as school principals, homeroom teachers, and students.